The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2166/wst.2021.237
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of nickel oxide nanoparticles using Allium cepa peels for degradation of Congo red direct dye: an environmental remedial approach

Abstract: Direct dyes are used in different textile operations and processings. The textile industries are disposing of unused direct dyes into the aquatic environment which is posing a serious alarming threat to aquatic lives. The current study deals with the synthesis of nickel oxide nanoparticles using Allium cepa peels aqueous extract. Nickel oxide nanoparticles (NiO-NPs) were characterized by SEM. Synthesized NiO-NPs were used to remove Congo red direct dye. Various experimental factors like concentration of dye &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Scientists are working on developing biologically produced nanoparticles derived from plant extracts [24][25][26][27][28]. Plant-assisted nanoparticles can also be used to cure a range of diseases [29].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists are working on developing biologically produced nanoparticles derived from plant extracts [24][25][26][27][28]. Plant-assisted nanoparticles can also be used to cure a range of diseases [29].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin dyestuff work as a ligand in the removal of copper and other metals from aqueous salt solutions [36].…”
Section: Fig 2 the Backbone Of A Flavonol [14]mentioning
confidence: 99%
“…It was observed that maximum decolorization value was 95.76% at 40˚C (Figure 6b). In this treatment process, decolorization ability of Reactive Brown 9 dye slowly concentrated as the temperature increased (Rafique et al, 2021). There is a reduction in adsorption efficiency at higher temperatures, possibly because of the phase conversion of catalyst with temperature promotion, which may decay in the surface area of catalyst (Lafta, 2015).…”
Section: Temperature Effect On Decolorization Of Reactive Brown 9 Dyementioning
confidence: 99%
“…COD and TOC reduction (%) values were found to be 88.56% and 85.34%, respectively at 50 minutes of contact time. Therefore, it may be expected that MgO nanoparticles not only get rid of color simply, but additionally lessen the COD and TOC of the dye solution to ensure mineralization progress (Kale and Kane, 2018;Kiran et al, 2020;Rafique et al, 2021).…”
Section: Mineralization Studymentioning
confidence: 99%